(untitled) (Innovaciones Educativas, 2021)
This paper aims to describe the personal meanings assigned to the term fair play by Costa Rican sixth-grade students. Deriving out of a quantitative and qualitative analysis of the answers to the problems associated with the notion of fair play, we describe the strategies used and the semiotic conflicts detected. Also, the obtained outcomes are compared with data gathered in previous research. In general, this paper shows an adequate understanding of the notion of fair play. However, a significant difficulty to justify winning according to each player’s hope of winning was found; they often justified their answers with additive strategies, which generated incorrect answers. Furthermore, a lower performance was obtained concerning the results reported in previous studies with subjects of the same age who did not receive education in the subject.